CORPORATE CRISIS COMMUNICATION IN THE AGE OF SOCIAL MEDIA: A LITERATURE REVIEW ON STRATEGIC ADAPTATION AND PUBLIC ENGAGEMENT - Kartikawati, Dwi; Dian Metha Ariyanti; Purnomo (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study explores the dynamics of corporate crisis communication in the digital age, with a particular focus on the role of social media platforms in shaping organizational strategies. Using a qualitative approach and library research method, the research systematically reviews academic literature, industry reports, and documented case studies to understand how corporations respond to crises in a hyper-connected environment. The study highlights how traditional theories such as Situational Crisis Communication Theory (SCCT) and Image Repair Theory (IRT) must be adapted to meet the demands of real-time, interactive, and ethically sensitive digital spaces. Through comparative analysis of successful and failed crisis responses—including global cases such as United Airlines and local cases such as Tokopedia—the research reveals that timely, transparent, and empathetic communication on social media significantly influences public perception and corporate reputation recovery. The findings emphasize that a well-designed digital crisis strategy must integrate technical responsiveness with human-centric values to restore trust and sustain long-term relationships with stakeholders. Keywords : crisis communication, corporate strategy, social media, digital reputation